VARIABILITAS MUSIMAN JENIS MAMALIA DI KAWASAN INDUSTRI SEMEN PT INDOCEMENT TUNGGAL PRAKARSA TBK UNIT PALIMANAN, JAWA BARAT - Kartono, Agus Priyono; Choirunnisa, Amalia; Prayogi, Kendy Danang; Chandra, Rufidi (JURNAL BIOLOGI INDONESIA, 2016)
ABSTRACTA study on seasonal variability of mammals species was carried out in the cement industrial area of PT Indocement Tunggal Prakarsa Tbk. Palimanan Plant, West Jawa. The combined action of climatic factors and habitat types have an important contribution to the diversity of mammals. Season conditions in the cement industrial and quarry area can be divided into the dry and rainy seasons. Eight main habitat types are present in the region: the conservation area of Mount Blindis, tree stands within the factory area, tree stands outside the factory area, area surrounding the pool/artificial lake, area of Jatropha curcas plantation, buffer zone, shrubs, and paddy fields in the cement industrial area and quarry. The objective of this study was to compare the diversity of mammals based on the season and habitat types. Total of mammals found are 17 species, comprising 10 species of aerial mammals (bats) and 7 species of terrestrial mammals. We found that species richness in the dry and rainy season was significantly different (p = 0.000). Dry season is richer (13 species, 105 individuals) than rainy season (12 species, 93 individuals). Index of mammals species diversity in the dry season is H'=1.65±0.12 with evenness index J'=0.64; while the rainy season is H'=1.87±0.10 with evenness index J'=0.75. Communities similarities of mammals between the dry season with the rainy season is 64%.Keywords: Mammals, bats, species richness, diversity, evenness, similarity community